What if I like it? Daily appraisal of technology-assisted supplemental work events and its effects on psychological detachment and work engagement - Kunz, Lea Katharina; Ducki, Antje; Hoppe, Annekatrin (Frontiers in Organizational Psychology, 2024)
Introduction Information and communication technologies (ICT) allow employees to engage in technology-assisted supplemental work (TASW), such as continuing work tasks and being contacted by supervisors or colleagues after their official working hours. Research has found that TASW can have positive and negative effects on employee wellbeing. Yet, it remains unclear under which circumstances TASW is beneficial or harmful. Building on appraisal theories, we hypothesized that a more positive appraisal of TASW events is related to higher levels of daily psychological detachment and work engagement. We further proposed that daily psychological detachment is positively associated with daily work engagement and mediates the relationship between appraisal of TASW events and daily work engagement. Methods To test our hypotheses, we conducted a diary study with two surveys per day over five consecutive workdays (N = 135; 245 daily observations). Results Results of multilevel path analysis showed that a more positive appraisal of TASW was positively related to work engagement. However, appraisal of TASW events was not associated with psychological detachment and, therefore, there was no mediating effect on work engagement. Discussion Our results contribute to existing research by investigating potential beneficial aspects of TASW and its effects on work engagement. Future research avenues and practical implications are discussed.